Strategies For Increasing Tourist Flow In Bukhara Region - Khalimov, Gayrat (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
this study comprehensively analyzed the priority directions for developing tourism in the city of Bukhara. It highlights strategies to increase tourist flow by strengthening marketing activities, improving tourism infrastructure, and enhancing transport connectivity. The importance of improving service quality, preserving cultural and historical sites, and presenting them using modern methods is also substantiated. The research emphasizes the necessity of diversifying tourism types and effectively utilizing digital technologies and online platforms. The proposed recommendations for expanding international cooperation aim to enhance the competitiveness of Bukhara city in the international tourism market.